A Biotin Micropatterned Surface Generated by Photodestruction Serves as a Novel Platform for Microtubule Organisation and DNA Hybridisation. Issue 6 (20th March 2013) - Biswas, Atanu; Saha, Abhijit; Jana, Batakrishna; Kurkute, Prashant; Mondal, Goutam; Ghosh, Surajit
<x xml:space="preserve">Abstract</x> Mask and capture: Photodestruction of parts of a biotin‐functionalised surface by shining UV light through a photomask produces a biotin micropattern. These micropatterns can selectively capture functional biotin‐tagged biomolecules/proteins such as microtubules and molecular beacons.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>